East Asian Buddhism and Korea’s Transnational Interactions and Influences - Cawley, Kevin N. (Religions, 2023)
No one can dispute the significant influence of Sinitic Buddhism in East Asia, but Korean Buddhists were also unquestionably close to the center of the development of different schools of Buddhism in mainland China, particularly in the Jiangnan region, which had historically drawn monks from the peninsula. This article will briefly cover the historical transnational Buddhist interactions between Korea and China, with an emphasis on doctrinal Buddhism, the significance of Ŭisang and Ǔich’ǒn, and the influence of Hangzhou’s Buddhist intellectual advancements. Even though the article’s main focus is on doctrinal contacts, we will also briefly discuss Chan Buddhism in China and how it influenced the texts and techniques of the Korean Sŏn (Zen) monk Chinul (1158–1210), who made an effort to integrate the doctrinal and meditational traditions, as did Ǔich’ǒn. This process of idea-cross-fertilization led to the Tripitaka Koreana, the largest collection of Buddhist texts in East Asia, created by Buddhists during the Koryŏ dynasty (918–1392), which is discussed below. This will aid in our understanding of these transnational exchanges and highlight the fact that Koreans were not only absorbing new ideas as they emerged in China, but they were also influencing them.